Visual enunciation and style - µ, Groupe (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
Thanks to notions like that of free variant, style can receive a semiotic definition. It be comes an individuating effect of the text, produced along the enunciation or during the reception of the latter, and presenting important hermeneutic functions. The present paper applies the concept of style to visual icons. Within this framework it is intimately connected to the process of transformation (viz. the relation existing between the referent and the iconic signifier). Any iconic statement,in effect, bears witness, not only to the referent, but also to the code constraints as well as to the structures of the emitting and receiving instances.
Keywords: Semiotics; iconicity